The Chinese economy - Morgan, Stephen L. (World economies., 2021)
Stephen Morgan provides a comprehensive analysis of China's unprecedented economic transformation and the specifics of its development, including issues such as well-being and human capital, inequality, ageing, urbanization and sustainability, consumerism, health, education and the environment.